2016
DOI: 10.1159/000450614
|View full text |Cite
|
Sign up to set email alerts
|

Precuneal Thickness and Depression in Parkinson Disease

Abstract: Background: Depression-related gray matter changes in Parkinson disease (PD) patients have been reported, although studies investigating cortical thickness in early-stage disease are lacking. Objective: We aimed to evaluate cortical changes related to depression in early-stage PD patients with an extensive neuropsychological evaluation. Methods: 17 PD patients and 22 healthy controls underwent a 1.5-T brain MR protocol, and voxel-wise differences in cortical thickness among patients with (n = 6) and without (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
0
8
4
Order By: Relevance
“…Anxiety and depressive disorders are common in PD, which are associated with structural and functional changes of multiple brain regions (Schrag and Taddei, 2017;Carey et al, 2021). In PD with mild to moderate depression, cortical thickness of the precuneus cortex was also significantly increased (Zanigni et al, 2017). However, in our cohort, we did not observe any significant correlations.…”
Section: Discussioncontrasting
confidence: 80%
“…Anxiety and depressive disorders are common in PD, which are associated with structural and functional changes of multiple brain regions (Schrag and Taddei, 2017;Carey et al, 2021). In PD with mild to moderate depression, cortical thickness of the precuneus cortex was also significantly increased (Zanigni et al, 2017). However, in our cohort, we did not observe any significant correlations.…”
Section: Discussioncontrasting
confidence: 80%
“…In addition to the regions in the corticolimbic system, we identified postcentral gyrus, precuneus, and temporal pole. These regions were also reported to be related to DPD patients [7,12,58]. The alteration in postcentral gyrus was associated with the cortical-basal ganglia circuit that is known as an important system that controls motor symptoms in PD patients [59].…”
Section: Discussionmentioning
confidence: 99%
“…It was also associated with cortical thinning in left temporal, anterior cingulate, right posterior cingulate and hippocampal cortices as well as thalamus volume shrinking over time, and higher scores of depressive symptoms at baseline correlated with a higher rate of cortical thinning longitudinally (Goto et al 2018 ; Hanganu et al 2017 ). Precuneus thinning was evident in PD patients with mild-moderate depression in early stages of disease (Zanigni et al 2017 ). Others reported smaller amygdala volumes but intact limbic connectivity (Surdhar et al 2012 ), and GM decrease in bilateral orbitofrontal, right temporal region and the limbic system (Feldmann et al 2008 ).…”
Section: Brain Structural Correlates Of Dpdmentioning
confidence: 99%
“…Both the dorsal raphe nucleus (serotonergic) and LC (noradrenergic) involved in premotor PD stages can lead to depletion of monoaminergic transporter systems in the basal ganglia-cortical loop linked to emotional control. These and changes of precuneal cortex thickness have been associated with depression in early PD (Borgonovo et al 2017 ; Zanigni et al 2017 ). Higher prevalence of pathological features in depressed vs non-depressed PD patients particularly in the catecholaminergic brain areas, LC (neuronal loss p = 0.08; gliosis p = 0.008), dorsal raphe nuclei (neuronal loss p < 0.05) and SNc (ns), but differences in amygdala and cortical regions suggested that DPD is more related to catecholaminergic than to serotonergic dysfunction (Frisina et al 2009 ), whereas LBs in the dorsal raphe nuclei in early PD implicated a serotonergic pathology in early DPD (Tan et al 2011 ), without a prominent role of dopaminergic degeneration (Maillet et al 2016 ).…”
Section: Combined Neurotransmitter Deficitsmentioning
confidence: 99%